PERGESERAN LAYANAN PERPUSTAKAAN PERGURUAN TINGGI MELALUI KONSEP VIRTUAL LIBRARY (Studi Kasus di Perpustakaan Universitas Mercu Buana Jatisampurna ) - Rengga Sendrian; Lailatur Rahmi (Shaut Al-Maktabah : Jurnal Perpustakaan, Arsip dan Dokumentasi, 2019)
The development of information technology in the end encourage librarians to increase the use of ICT within the administering College Library. His goal was to be able to run the College Library functions with either IE as the brain knowledge and supporting the learning process through the availability of existing collections in the library. Librarians are beginning to understand that the service given by the library against pemustakanya can continue to improve in so well that pemustaka especially in access to information. The purpose of access to information in the era of the revolution Indutsri 4.0 at this time is how information can be received by pemustaka in quick time effectively and efficiently. Implementation of the virtual library on the College Library has the ability in solving problems, information explosion of the presence information and the influence of development of information technology. College Library's needs clearly felt it is important to use the right information technology, so that it can access a variety of information from around the world.